El Recargo Tributario del 20% según el Art. 90 del Código Orgánico Tributario afecta al desarrollo y al progreso del Sujeto Pasivo o Contribuyente - Riascos Cabrera, Raúl David (2016)
In our country the tributary activity is very important for the Ecuadorian society, since he/she has for primordial purpose the one of financing the public expense and this way the State can fulfill its objectives outlined to achieve the good one to live for all the and the Ecuadorians. They have been carried out a series of reformations to the normative one tributary, among these he/she incorporated the well-known figure as overcharge, settled down in Art. 2 of the Reformatory Law for the Tributary Justness that Art modifies. 90 of the Organic Tributary Code with which several interpretations arose, it is hence that with this study he/she tried to be defined the nature clearly and to analyze if it affects or not to the passive fellows or taxpayers leaving of the different focuses. The incorporate overcharge to the now Organic Tributary Code, points out that once a determination takes place on behalf of the active fellow, that is to say of the Tributary Administration, the same one will cause this way an overcharge of 20% on the obligation certain. The problem with the overcharge resides in the fact of the confusion that exists in relation to this figure and to the interests, from the point of view of the Tributary Administration whose objective is to increase the collections and that the taxpayers pay in its entirety the taxes, the overcharge is resarcitorio; while 6 for the taxpayers a double sanction exists, since this it comes from the declaration lack to that which sum a ticket and the interests of the main obligation. The overcharge is applied since from an unjust way when establishing 20% he/she is not defined the form like to end up incorporating this percentage since is not considered errors in the declaration of the tributary obligation that which violates the principle of proportionality. He/she will be carried out a study of the Constitution and the normative one legal effective in tributary matter as well as the doctrinal postulates, the existent jurisprudence around the topic stops this way to formulate the possible solutions that they will be proposed. We should consider the quantity of tributary loads that at the moment exist in our country and to wonder if all these settled down in harmony with the principles tributary generals settled down in the Organic Tributary Code and the tributary constitutional principles settled down in the Article 300 of the Constitution of the Republic of Ecuador, guarantors of the rights of people; such it is the case of the overcharge of 20% settled down in the parenthesis second of the Article 90 of the Organic Tributary Code, which burdens to the determinations of the Tributary Obligation made by the active fellow of this. 7 To this overcharge he/she believes it to him, without defining their artificial nature, without determining their environment neither application rules and worse still without analyzing the consequences that he/she would have in our juridical classification due to the legal existent holes on this figure and the consequences that the passive fellow of the Tributary obligation can suffer, when impacting negatively in his patrimony and for ende affecting the development and progress of the passive fellow or taxpayer.